IMPLEMENTATION AND EVALUATION OF AN IOT-BASED LEARNING MODULE ON SOIL QUALITY IN RELATION TO STUDENTS’ SCIENTIFIC COMMUNICATION SKILLS - Isyatun Rodiah; Wawan Kurniawan; Dian Pertiwi Rasmi (Physics and Science Education Journal (PSEJ), 2026)
This study aims to examine the implementation and evaluation of the use of an Internet of Things (IoT)-based learning module on soil quality material in supporting students’ scientific communication skills. This research is part of a development study using the ADDIE model, focusing on the implementation and evaluation stages, and employing a quantitative descriptive approach. The research subjects were 15 students enrolled in the Environmental Physics course. The instrument used was a scientific communication skills questionnaire covering both verbal and non-verbal aspects, which had been validated by experts. Data analysis was conducted using descriptive statistics in the form of percentages and mean scores. The results showed that students’ scientific communication skills were in the very good category, with an average score of 84%, where verbal communication was 83% and non-verbal communication was 85%. These findings indicate a tendency of a relationship between the use of IoT-based modules and students’ scientific communication skills, although the results are still limited to a small sample and descriptive analysis.